Changes in Emotional-Behavioral Functioning Among Pre-school Children Following the Initial Stage Danish COVID-19 Lockdown and Home Confinement - Specht, Ina Olmer; Rohde, Jeanett Friis; Nielsen, Ann-Kristine; Larsen, Sofus Christian; Heitmann, Berit Lilienthal (Frontiers in Psychology, 2021)
Background: Unintended negative outcomes on child behavior due to lockdown and home confinement following the COVID-19 pandemic needs highlighting to effectively address these issues in the current and future health crises. Methods: This study was a sub-study of the longitudinal ODIN-study. The objectives of the current study were to determine whether the Danish lockdown and home confinement following the COVID-19 pandemic affected changes in emotional-behavioral functioning of pre-school-aged children using the validated Strength and Difficulties Questionnaire (SDQ) answered by parents shortly before lockdown and three weeks into lockdown, and moreover, to examine whether baseline family and social characteristics could predict development in child emotional-behavioral functioning during lockdown. Results: Parents of 40(82%) children with a mean(SD) age of 5.0(0.7) completed the baseline questionnaire and the lockdown follow-up questionnaire. The SDQ-Total difficulties score (SDQ-TD) and Prosocial Behavioral score (PSB) changed significantly from pre- to lockdown [SDQ-TD mean(SD): 6.0(3.8) and 7.9(5.2); P=.02, respectively and PSB mean(SD): 8.5(1.4) and 7.9(1.5); P=.03, respectively]. Attending leisure time activities before lockdown was a predicting factor of changes to the worse in the children’s SDQ-TD scores, with a mean difference in SDQ-TD between those with and without activities of 3.16 (95%CI 0.27-6.12); P=.03. Conclusions: This small study confirmed a small negative development in child emotional-behavioral functioning during the COVID-19 lockdown, potentially due to parental stress. Although these results might not be generalizable due to small sample size and selected population, the results point to a need of a greater awareness of child mental wellbeing during a lockdown situation.